Analysis of Indonesian Consumer Online Shopping Behavior During the Covid-19 Pandemic: A Shopee Case Study - Firmandani, Wahyu; Sya’bania, Anisa Fitri; Abdani, Fadlil; Madani, Eltin (Fakultas Pendidikan Ekonomi dan Bisnis, 2021)
Covid-19 affects and changes almost all aspects of life. Change is not only for awareness to have a healthy lifestyle but also people's preferences in doing online shopping. Many indicators influence changes in society in making decisions, especially in making online purchases. Because of this, in this research the needs of people with changing preferences after Covid-19, Shopee as one of the giant e-commerce in Indonesia must also adapt to existing conditions. This research was conducted using a descriptive method based on the results of a questionnaire to several samples witk purposive sampling of Indonesian society in metropolitan cities to obtain the findings and expected results of this study. Apart from using primary data, this research is also supported by reliable secondary data. The results of this study are to determine changes in people's preferences for online shopping after the Covid-19 pandemic. The research is limited to a sample of Indonesian people and Shopee as e-commerce platform. This research is expected to help Shopee, other e-commerce and other online seller to understand changes in customer demand and perception during Covid-19 to increase their sales and lead to customer satisfaction.Keyword: Covid19, Perception, Online Shopping.